REVISITING GENDER TOUGHT IN ISLAMIC STUDIES - Karimatul Khasanah (Teosofia: Indonesian Journal of Islamic Mysticism, 2017)
Women issue viewed from religions perspective will be always interesting to study. It is because religion often does "not bridging" the role of women as creatures who share a humanitarian and divine mission, like men, instead it makes the position of women subordinated and marginalized. responding to the discourse on gender, this paper tries to find the root of the problem out by making modern thinkers as a foothold, namely AminaWadud and KhaledAbou El-Fadl. AminaWadud introduces tauhidi hermeneutics which can be used as a paradigm and methodology. Meanwhile El-Fadl introduces a dialogical hermeneutics to bridge the imbalance of subjectivity elements that often occur in gender interpretation.